A Hydrophobic‐Interaction‐Based Mechanism Triggers Docking between the SARS‐CoV‐2 Spike and Angiotensin‐Converting Enzyme 2 (Global Challenges 12/2020). Issue 12 (3rd December 2020) - Li, Jiacheng; Ma, Xiaoliang; Guo, Shuai; Hou, Chengyu; Shi, Liping; Zhang, Hongchi; Zheng, Bing; Liao, Chenchen; Yang, Lin; Ye, Lin; He, Xiaodong
Abstract : In article number 2000067 Lin Yang and co‐workers find that the hydrophobic interaction between the SARS‐CoV‐2 spike protein and the ACE2 protein is significantly greater than that between the SARS‐CoV spike protein and the ACE2 protein. At the docking site, the hydrophobic portions of the hydrophilic side chains of SARS‐CoV‐2 S are found to be involved in the hydrophobic interaction between the SARS‐CoV‐2 spike protein and ACE2.